Effects of Weathered Soil Parent Materials on Merlot Grapevines Grafted onto 110 Richter and 101-14Mgt Rootstocks - Wooldridge, J.; Olivier, M.P. (South African Journal of Enology and Viticulture, 2016)
In a trial under semi-controlled conditions, Merlot grapevines on 101-14Mgt and 110 Richter (110R) rootstocks were grown in virgin soils developed in highly weathered parent materials derived mainly from granite and metasediment (shale). Each soil was irrigated at c. -0.075 MPa. The clay fractions of both soils were dominated by kaolinite. Lime and P were supplied, but no K. Bray II soil K levels from both parent materials were similar in the field state, but lower in the shale than in the granite when averaged over the trial period. Petiole K concentrations did not differ between rootstocks on the granite, but on the shale soils were higher in the vines on 101-14Mgt than on 110R. The granite x 101-14Mgt treatment significantly promoted (p ≤ 0.05) greater trunk circumferences, cane mass, leaf areas and overall wine quality than the shale x 110R treatment. Yields from grapevines in the granite x 110R and granite x 101-14Mgt treatments did not differ significantly. However, the granite x 101-14Mgt treatment produced higher yields than the shale x 101-14Mgt and shale x 110R treatments. These differences were attributed to an interaction between the soil and rootstock, with K availability and uptake as contributory factors.